2008
DOI: 10.1111/j.1460-9568.2007.06004.x
|View full text |Cite
|
Sign up to set email alerts
|

A cell adhesion molecule mimetic, FGL peptide, induces alterations in synapse and dendritic spine structure in the dentate gyrus of aged rats: a three‐dimensional ultrastructural study

Abstract: The FGL peptide is a neural cell adhesion molecule (NCAM) mimetic comprising a 15-amino-acid-long sequence of the FG loop region of the second fibronectin type III module of NCAM. It corresponds to the binding site of NCAM for the fibroblast growth factor receptor 1. FGL improves cognitive function through enhancement of synaptic function. We examined the effect of FGL on synaptic and dendritic structure in the brains of aged (22-month-old) rats that were injected subcutaneously (8 mg/kg) at 2-day intervals un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 63 publications
(132 reference statements)
4
24
0
Order By: Relevance
“…(Popov et al, 2004(Popov et al, , 2008Popov and Stewart, 2009). However, a more detailed examination of the tissue showed prominent ultrastructural changes after kindling in the right hippocampus.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(Popov et al, 2004(Popov et al, , 2008Popov and Stewart, 2009). However, a more detailed examination of the tissue showed prominent ultrastructural changes after kindling in the right hippocampus.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…No changes were found in the size of mushroom and thin spines and their PSDs in MPP-9 TR compared with WT rats. To describe possible changes in spine shape in the active zone area, we analysed the curvature of the PSD area of mushroom and thin spines [as described in the Materials and Methods and in Popov et al (Popov et al, 2008)] but no significant changes were found in spine curvature. The curvature of mushroom spines in the PSD area was 8 50.6148;P50.4768); the curvature of thin spines in the PSD area was, respectively, -6.25¡0.53˚for WT and -1.34¡0.62˚for MMP-9 TR rats (F 1,8 51.1313; P50.3474).…”
Section: Resultsmentioning
confidence: 99%
“…Shaft synapses are a fourth category where the synapse contacts directly the dendritic shaft. There were three animals in each group for the three-dimensional analyses, which were made from the stratum radiatum of CA1; 25 thin and 25 mushroom spines were reconstructed to analyse spine volume, surface area and curvature of the PSD, as described previously (Popov et al, 2008). The volume and surface area of PSDs on these reconstructed spines were also analysed.…”
Section: Digital Reconstructive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…FGL has indeed been shown to influence connectivity in the DG (Popov et al 2008;Stewart et al 2010), as well as in hippocampal-dependent memories (Cambon et al 2004;Secher et al 2009); further, FGFR1 have been shown to influence plasticity in the DG (Zhao et al 2007). The cellular mechanisms associated with long-term potentiation (LTP) in the first hours following its induction are thought to primarily involve posttranslational modifications (Bliss and Collingridge 1993).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%